STRATEGI INKLUSIF GURU PAI DALAM MENGAKOMODASI GAYA BELAJAR DAN KEBUTUHAN SPESIFIK SISWA DI SEKOLAH REGULER: STUDI FENOMENOLOGI DI TIGA SMA INKLUSI DI KABUPATEN BUNGO, JAMBI - Kurniawan, Sugeng; Sriani; Mulyani, Ranti; Baili; Sabli, Muhammad; Mabruri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The implementation of inclusive education in regular schools requires Islamic Religious Education (PAI) teachers to develop pedagogical strategies responsive to diverse learning styles and specific student needs. This study aims to explore the lived experiences of PAI teachers in designing, implementing, and reflecting on inclusive strategies in regular classrooms that accommodate students with special needs in Bungo Regency, Jambi. The research employed a qualitative descriptive phenomenology design using Colaizzi’s seven-step analysis procedure. Subjects consisted of 12 PAI teachers from three inclusive public high schools in Bungo Regency, selected through purposive sampling based on criteria of at least three years of experience and teaching load in inclusive classes. Data were collected through semi-structured in-depth interviews, participatory observation, learning document analysis, and member checking. Analysis revealed four essential themes: (1) diagnostic mapping that transcends clinical labels toward holistic learning profiles, (2) flexible instructional design based on Universal Design for Learning (UDL) with contextual adaptations in worship and moral content, (3) structured collaborative ecosystems adapted to regional resource constraints, and (4) spiritual-emotional anchoring integrating Islamic values with Malay-Jambi local wisdom. Findings indicate that PAI teachers' inclusive strategies are not merely technical-pedagogical but transformative practices that unify differentiation competencies, multiprofessional collaboration, and internalization of religious values to create equitable, meaningful, and humane learning spaces in a semi-urban context. The study recommends strengthening inclusive pedagogical competencies in teacher professional education, developing contextual UDL-based PAI adaptation modules, and Bungo Regency Education Office policies that facilitate collaboration time and sustained mentoring. Results contribute to enriching the literature on inclusive PAI pedagogy and strengthening inclusive education policy implementation in the Jambi region.